Penerapan Teknik Framing dalam Editing Video Feature - Iwan Koswara; Rinda Aunillah; Ufayra Syahidina (Comit: Communication, Information and Technology Journal, 2024)
This article discussed the application of framing techniques during the video feature editing process, focusing on how framing influenced the presentation of the story to the audience. This study was motivated by the transformation of journalism in the digital era, where video features became one of the popular reporting formats. Video features allowed for an in-depth exploration of topics and provided broader context. Framing techniques were used to select and highlight certain aspects within the video, shaping audience perception and understanding. The video feature editing process involved several stages, including clip selection, emphasis on key aspects, exclusion of irrelevant elements, and the elaboration of additional information. This study employed a descriptive analytical method with a case study on the video feature “Kuliner Legendaris: Sukses Melintasi Dekade”. The analysis results showed that effective framing techniques could guide public opinion, build empathy, and encourage action from the audience. Video editors played a key role in applying framing techniques to ensure the story conveyed matched the narrative's purpose.